Manual exchange transfusion for severe imported falciparum malaria: a retrospective study - Jinfeng Lin; Xiaoying Huang; Gang Qin; Suyan Zhang; Weiwei Sun; Yadong Wang; Ke Ren; Junxian Xu; Xudong Han (Malaria Journal, 2018)
Abstract Background This study was designed to evaluate the efficacy of exchange transfusion in patients with severe imported falciparum malaria. Twelve patients who met the diagnostic criteria for severe malaria were treated with exchange transfusion 14 times according to a conventional anti-malarial treatment. This study evaluated the efficacy of exchange transfusion for severe imported falciparum malaria. Methods Clinical data of severe imported falciparum malaria patients admitted to the intensive care unit (ICU) of Nantong Third People’s Hospital from January 2007 to December 2016 were investigated in this retrospective study. Patients were divided into the intervention group, which received exchange transfusion, and the control group. This study assessed parasite clearance and outcomes of the two groups, and levels of erythrocytes, haemoglobin, platelets, coagulation, liver function, lactate, C-reactive protein, and procalcitonin, before and after exchange transfusion in the intervention group. Results There was no significant difference in the severity of admitted patients. Exchange transfusion was successfully applied 14 times in the intervention group. Differences in the levels of erythrocytes, haemoglobin and platelets did not reach statistical significance. Exchange transfusion improved coagulation, liver function, lactic acid, C-reactive protein, and procalcitonin. No differences were observed in parasite clearance, ICU and hospital length of stay, in-hospital mortality, and costs of hospitalization between the two groups. Conclusion Exchange transfusion as adjunctive therapy for severe malaria was observed to be safe in this setting. Exchange transfusion can improve liver function and coagulation and reduce inflammation, but it failed to improve parasite clearance and the outcomes of severe imported falciparum malaria in this case series.